Performance of A Horizontal Cylinder Type Rotary Dryer for Drying Process ofOrganic Compost from Solid Waste Cocoa Pod - Sukrisno Widyotomo; Sri Mulato; H Ahmad; Siswijanto Siswijanto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2008)
Cocoa pod husk is the bigest component of cocoa pod, about 70% of total ht of mature pod, and to potentially used as organic compost source. Poten tial solid waste of cocoa pod husk from a cocoa processing centre is about 15— 22 m3/ha/year. A cocoa plantation needs about 20—30 ton/ha/year of organic matters. One of important steps in compos processing technology of cocoa pod solid waste is drying process. Organic compost with 20% moisture content is more easy in handling, application, storage and distribution. Indonesian Coffee and Cocoa Research Institute has designed and tested a horizontal cylinder type rotary dryer for drying process of organic compos from solid waste cocoa pod with kerosene burner as energy sources. The objective of this research is to study performance of a horizontal cylinder type rotary dryer using kerosene burner as energy source for drying process of organic compost from solid waste cocoa pod. The material used was solid waste cocoa pod with 70—75% moisture content (wet basis), 70% size particle larger than 4.76 mm, and 30% size particle less than 4.76 mm, 690—695 kg/m3 bulk density. Drying process temperatures treatment were 60OC, 80OC, and 100OC, and cylinder rotary speed treatments were 7 rpm, 10 rpm, dan 16 rpm. The results showed that dryer had capacity about 102—150 kg/h depend on drying temperature and cylinder rotary speed. Optimum operation condition at 100OC drying temperature, and 10 rpm cylinder rotary speed with drying time to reach final moisture content of 20% was 1,6 h, capacity 136,14 kg/ h, bulk density 410 kg/m3, porocity 45,15%, kerosene consumption as energy source was 2,57 l/h, and drying efficiency 68,34%. Key words : cocoa, drying, rotary dryer, compost, waste